Microsporum canis and Sporothrix schenckii: fungi causing skin infections in cats - Mohd-Khlubi, Aina Nazurah; Omar, Sharina; Bejo, Siti Khairani; Megat Abd Rani, Puteri Azaziah (Universiti Putra Malaysia Press, 2024)
Companion animals such as cats help to reduce stress among people as they delight their owners in their ways. Good management and hygiene practices of pets help in keeping them in a healthy condition. Nevertheless, since fungal infection develops rapidly, there is a high tendency for them to get infected. The paucity of data regarding skin mycoses among cats in Malaysia leads to this study. Private veterinary clinics from the Central Region of Peninsular Malaysia were approached for participation in this study. Sampling was conducted for one year, collecting hair plucked, skin scrapings, and swabs from lesions of the cats with skin problems and inoculating onto Sabouraud Dextrose Agar media. Diagnosing the fungal colony was conducted through a direct examination method using lactophenol cotton blue stain and molecular identification of the isolates using polymerase chain reaction targeting the fungi species’ internal transcribed spacer region and β-tubulin gene. Of the 127 cats, 93 were positively infected, mainly with Microsporum canis (n = 38) and Sporothrix schenckii (n = 26). Saprophytic fungi detected on cats were Alternaria sp., Aspergillus sp., Candida sp., Chaetomium sp., Chrysosporium sp., Curvularia sp., Fusarium sp., Geotrichum sp., Penicillium sp., Talaromyces sp., Trichoderma sp., Trichosporon sp., and Xylaria sp. This finding represents the number of cats infected with fungal dermatitis in Selangor, Negeri Sembilan, the Federal Territory of Kuala Lumpur, and Putrajaya.